Atom probe study of chromium oxide spinels formed during intergranular corrosion. (1st April 2015) - La Fontaine, Alexandre; Yen, Hung-Wei; Felfer, Peter J.; Ringer, Simon P.; Cairney, Julie M.
Abstract : Atom probe microscopy has been used to study the inhomogeneous nature of chromium oxide spinels in intergranular corrosion of a 253 MA austenitic stainless steel after thermal cycling up to 970 °C in air. The results indicate that the non-continuous character of the spinel layers originates from nanoscale phases such as iron-rich oxides along the chromite grain boundaries and silicate particles. Their role in the rate of intergranular corrosion is discussed.